Comparison of Post-Operative Port Site Pain Following Laparoscopic Cholecystectomy: Umbilical Port versus Epigastric Port Retrieval - Salunke, Tushar Laxman (Journal of Biomedical and Pharmaceutical Research, 2022)
This study aims to compare post-operative port site pain associated with gallbladder retrieval through the umbilical port versus the epigastric port following laparoscopic cholecystectomy. Laparoscopic cholecystectomy is the gold standard for managing symptomatic gallbladder disease; however, the choice of retrieval site may influence post-operative pain and recovery. A randomized controlled trial was conducted with 100 patients undergoing elective laparoscopic cholecystectomy. Patients were equally assigned to two groups: one with gallbladder retrieval via the umbilical port and the other via the epigastric port. Post-operative pain was assessed using a visual analog scale (VAS) at 24 hours, 48 hours, and one week post-surgery. Results indicated that patients in the umbilical port retrieval group experienced significantly lower pain scores at 24 hours (3.2 vs. 5.1, p < 0.01) and 48 hours (2.5 vs. 4.3, p < 0.05) compared to those in the epigastric port group. By one week, the pain difference was negligible. These findings suggest that umbilical port retrieval may be associated with less post-operative pain in the immediate post-operative period, potentially enhancing patient recovery. Keywords: laparoscopic cholecystectomy, post-operative pain, umbilical port, epigastric port, gallbladder retrieval.